Combustion Characteristics and Combustion Kinetics of Dry Distillation Coal and Pine Tar - Bo Chen; Bo Liu; Zhangming Shi (International Journal of Aerospace Engineering)
The samples of dry distillation pine tar and coal tar were investigated by TG-DTG-DSC, and the combustion characteristics and combustion kinetics of the samples were studied. The results show that there exist two significant mass loss peak and endothermic peak in the combustion of dry distillation coal tar and pine tar, which, respectively, means the volatile hydrocarbon combustion and heavy hydrocarbon combustion. At the first DTG peak range, the activation energy of dry distillation pine tar and coal tar is about the same at the initial stage (before DTG peak). Activation energy of the dry distillation pine tar increases sharply while that of dry distillation coal tar has little changes on the subsequent stage (after DTG peak). Dry distillated coal tar has better ignition performance, combustible characteristic, combustible stability, and integrated combustion characteristic, but difficult to burnout compared to the dry distillation pine tar.